Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702448
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Deictic Gestures to Support Telepresence on Wall-sized Displays

Abstract: International audienceWe present a controlled experiment assessing how accurately a user can interpret the video feed of a remote user showing a shared object on a large wall-sized display by looking at it or by looking and pointing at it. We analyze distance and angle errors and how sensitive they are to the relative position between the remote viewer and the video feed. We show that users can accurately determine the target, that eye gaze alone is more accurate than when combined with the hand, and that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Wong and Gutwin (2010) looked at how people produce and understand pointing gestures when interacting with collaborative virtual environments. Avellino et al (2015) also investigated how accurately users can understand remote pointing from video footage on a large wallsized display. Systems such as HyperMirror try to allow deictic communication using a mirror metaphor that places local and remote partners in a joint "mirror" space (cf.…”
Section: Remote Communicationmentioning
confidence: 99%
“…Wong and Gutwin (2010) looked at how people produce and understand pointing gestures when interacting with collaborative virtual environments. Avellino et al (2015) also investigated how accurately users can understand remote pointing from video footage on a large wallsized display. Systems such as HyperMirror try to allow deictic communication using a mirror metaphor that places local and remote partners in a joint "mirror" space (cf.…”
Section: Remote Communicationmentioning
confidence: 99%
“…They also compared this technique with the a 3D virtual environment of GAZE [1]. Finally, Avellino et al [31] showed that video can be used to convey gaze and deictic gestures toward shared digital content in large wall-sized displays.…”
Section: Gaze Support For Shared Virtual Artifactsmentioning
confidence: 99%
“…Twelve participants (7 male), aged 22 to 33 (median = 25), with backgrounds from computer science, interaction design, and social science participated in the study. This sample size is the average one reported in CHI studies [38] and also used in related work [17,31]. Pilot studies determined that effects are strong enough to be observed with this sample size.…”
Section: Participantsmentioning
confidence: 99%
“…Wong and Gutwin (2010) looked at how people produce and understand pointing gestures when interacting with collaborative virtual environments. Avellino et al (2015) investigated how accurately users can understand remote pointing from video footage on a large wall-sized display. Systems such as HyperMirror try to tackle issues such as deictic communication by using a mirror metaphor that places local and remote partners in a joint 'mirror' space (cf.…”
Section: Remote Communicationmentioning
confidence: 99%